The age and formation mechanisms of Late Triassic fissure deposits, Gloucestershire, England: Comments on Mussini, G. et al. (2020). Anatomy of a Late Triassic Bristol fissure: Tytherington fissure 2. Issue 1 (February 2021) - Walkden, Gordon M.; Fraser, Nicholas C.; Simms, Michael J.
Abstract: In the Late Triassic the landscape NE of present-day Bristol, SW England was dominated by Carboniferous Limestone ridges and cuestas that became progressively buried by continental Mercia Mudstones and finally inundated during the Rhaetian marine transgression. Mussini et al. (2020) adopt the assertions of earlier collaborators back to Whiteside and Marshall (2008) that terrestrial vertebrate assemblages from sediments contained within karstic fissure systems in the former limestone ridges at Cromhall, Tytherington and elsewhere are restricted to the Rhaetian. We review and reject the sedimentological, stratigraphic, geomorphological and topographic arguments for this and reassert a long pre-Rhaetian (Norian) history for the vertebrate-bearing fissure systems at both Tytherington and Cromhall. We also reject the contemporaneous Rhaetian freshwater-seawater mixing zone dissolution model for the fissure systems adopted by Mussini et al. (2020) and reaffirm that the Tytherington and Cromhall fissures developed as conduit caves with a long Triassic history. Applying a new regional study of the Rhaetian transgressive surface, we also show that whilst the fissures at Cromhall remained sealed after the Norian, those at nearby Tytherington were re-exposed in the Late Rhaetian. Already partially filled with Norian sediments, the Tytherington fissures were subject to reworking on the seabed. Internal collapses, probably triggered by well documented repeated regional seismicity, led to the chaotic state of the Tytherington fills when downward moving Rhaetian marine components came to lie amongst and mix with earlier Norian terrestrial sediments. The vertebrate associations in the Tytherington fissures therefore contain a substantial Rhaetian input whilst those at Cromhall do not.